A Case Report of Variant Origin of Left Vertebral Artery from Aortic Arch and its Embryological Explanation - Bahman Jalali Kondori; Elham Rahimian; Mohammad Hossein Asadi; Majid Reza Tahsini (Negah Institute for Scientific Communication, 2014)
Vertebral artery is the first branch of subclavian artery. It merges with the same artery of the opposite side to form basilar artery and becomes one of the important source of blood supply to the brain. Variation in the origin of left vertebral artery was found in 65 year old female during magnetic resonance angiography of the neck vessels. It originated from aortic arch and was longer as compared with the right vertebral artery. Its further course was as usual. Awareness of such variations is important in supra-aortic vascular surgery and is clinically significant during diagnostic procedures like angiographi.